Análise estratigráfica e paleomagnética da Bacia de Lavras da Mangabeira - Cerqueira, João Carlos [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The Lavras da Mangabeira Basin, located in the State of Ceará, is a set of small sedimentary basins developed during the Gondwana mesozoic evolution. It belongs to the group of Interior Basins in the Northeast, which have increased detailing to understand the rifting event in the Cretaceous. Despite this, the Lavras da Mangabeira Basin has its stratigraphy and tectonic-sedimentary evolution little investigated, resulting from the scarcity of literature and publications focused on it. The present work of completion of course aims to supply the lack of stratigraphic knowledge and of the tectonic-sedimentary evolution of the basin, through stratigraphic and paleomagnetic analysis, in addition to a brief discussion on its structural geology. The stratigraphic analysis was based on fieldwork, facies description and association, columnar surveys, paleocurrent measurements and measurement of the thickness of the sedimentary packages. The paleomagnetic analysis made a comparison between paleomagnetic poles and virtual geomagnetic poles of the basin units with the apparent path of the paleomagnetic pole of the Amazonian Craton. The stratigraphic surveys collaborated in the revision of the Iborepi Formation, Serrote do Limoeiro Formation, diabase Lavras da Mangabeira and the establishment of a new one, named Mescla Formation. The Iborepi Formation is the basal unit, it is found on a lithological discordance with the basement, it has an sand conglomeratic character of an interlaced river and it has an average paleocurrent vector for NNW. The Serrote do Limoeiro Formation has layers of fine lake facies at the base, with intercalation between these and sandy facies from meandering river to the top, in addition to some eolic sandstone, presenting very scattered paleocurrents. The Mescla Formation is in erosive contact at the base and is composed of conglomeratic sandstones and interglomerate river sandstones, with paleocurrent indicating a flow to the NW and intense deformation at the top. Diabase Lavras da Mangabeira was reinterpreted as intrusive, due to its placement in sedimentary packages. The formations are much thicker than the literature studies, reaching up to five times greater. The basin was also divided into sectors, term indicating that they were previously a single basin, as it presented the same evolution and vertical stacking. The paleomagnetism resulted in ages of the Iborepi (PermianTriassic), Serrote do Limoeiro (Jurassic-Cretaceous) and Mescla (JurassicCretaceous) formations, in addition, through the diabase's paleomagnetic pole, to identifying a clockwise rotation of 20º of the basin, younger than 200 Ma (diabase radiometric age) and older than the Cretaceous. The tectonic-sedimentary evolution of the basin had a first phase of sedimentation linked to the local Afro-Brazilian Depression and with the opening of the neo-Triassic-Atlantic Jurassic Central Atlantic. A second phase of sedimentation is linked to the pre-rift phases of the Gondwana break up, with the tilting of the layers and dismemberment of the basin in the post-rift

A Bacia de Lavras da Mangabeira, localizada no Estado do Ceará, é um conjunto de pequenas bacias sedimentares desenvolvidas durante a evolução mesozoica do Gondwana. Ela pertence ao grupo de Bacias Interiores do Nordeste, as quais possuem crescente detalhamento para a compreensão do evento de rifteamento no Cretáceo. Apesar disso, a Bacia de Lavras da Mangabeira possui sua estratigrafia e evolução tectonossedimentar pouco investigada, resultante da escassez de literaturas e publicações focadas nela. O presente trabalho de conclusão de curso tem como objetivo suprir a falta conhecimentos estratigráficos e da evolução tectonossedimentar da bacia, através da análise estratigráfica e paleomagnética, além de uma breve discussão sobre sua geologia estrutural. A análise estratigráfica se baseou em trabalhos de campo, descrição e correlação de fácies, levantamento de seções colunares, medidas de paleocorrente e mensuração da espessura dos pacotes sedimentares. Já a análise paleomagnética realizou a comparação dos paleopolos magnéticos e polos geomagnéticos virtuais das unidades da bacia com o caminho aparente do polo paleomagnético do Cráton Amazônico. Os levantamentos estratigráficos colaboraram na revisão da Formação Iborepi, Formação Serrote do Limoeiro, Diabásio Lavras da Mangabeira e estabelecimento de uma nova, nomeada de Formação Mescla. A Formação Iborepi é a unidade basal, se encontra sobre uma discordância litológica com o embasamento, possui caráter arenoconglomerático de rio entrelaçado e possui vetor médio de paleocorrente para NNW. A Formação Serrote do Limoeiro possui camadas de fácies finas lacustres na base, com intercalação entre estas e fácies arenosas de rio meandrante para o topo, além de alguns arenitos eólicos, apresentando paleocorrentes muito dispersas. A Formação Mescla está em contato erosivo na base e é composta por arenitos e arenitos conglomeráticos de rio entrelaçado, com paleocorrente indicando um fluxo para NW e intensa deformação no topo. O Diabásio Lavras da Mangabeira foi interpretado como de caráter intrusivo, devido sua colocação nos pacotes sedimentares. As formações são muito mais espessas do que a literatura propõe, chegando a ser até cinco vezes maiores. A bacia foi também recompartimentada em setores, termo que indica que anteriormente eram uma única bacia, por apresentarem a mesma evolução e empilhamento vertical. O paleomagnetismo resultou em idades das formações Iborepi (Permiano-Triássico), Serrote do Limoeiro (Jurássico-Cretáceo) e Mescla (Jurássico-Cretáceo), além de identificar, através do paleopolo magnético do diabásio, uma rotação horária de 20º da bacia, mais nova que 200 Ma (idade radiométrica do diabásio) e mais velha que o Cretáceo. A evolução tectonossedimentar da bacia teve uma primeira fase de sedimentação atrelada à Depressão Afro-Brasileira local e com a abertura do Atlântico Central neotriássica-eojurássica. A segunda fase sedimentação está atrelada às fases pré-rifte da quebra do Gondwana, com o basculamento das camadas e desmembramento da bacia no pós-rifte.
Stratigraphic and paleomagnetic analysis of the Lavras da Mangabeira Basin
Keywords: Stratigraphy; Paleomagnetism; Mesozoic; Lavras da Mangabeira Basin; Estratigrafia; Paleomagnetismo; Mesozoico; Bacia de Lavras da Mangabeira